Relational autonomy and rape - Herring, J (Hart Publishing, 2009)
Jack bauer, james Bond, Jason Bourne: these are the male icons of our age. These rugged isolated conquerors struggle against the powers of the anonymous authorities. Bravely putting love of country before love of women, against insurmountable odds, they battle through. Leaving broken hearts wherever they go, they emerge bloodied, but victorious at the end of the day. Such men are seen by some as the epitome of the modern autonomous hero. Fighting free from the strings that bind and the forces that oppress, they emerge free men. Yet this image of ‘Super-Detached Man’ is a fiction (Chen-Wishart, 2006). More than that, he is a ‘thoroughly noxious concept’ (Hoagland, 1989, p 144).